A case analysis of registering research activity for institutional benefit - Rumsey, S (Elsevier, 2010)
Those in senior managerial positions and working in central services in higher education institutions (HEIs) need data about research activities. Such data is used by these individuals to assist their planning and reporting, for promoting the institution, and to enable them to identify opportunities for funding. This article describes the requirements for research activity information of senior managers and administrative staff at a large, research intensive HEI in the UK. A pilot registry for research activity data and exemplar web services that it supports have been created as part of a project designed to address some of those needs. The project was born out of the development of an institutional repository and uses a solution based on semantic web technologies. Developments are considered against the backdrop of change in current research information management activities.